Feasibility of Magnetoencephalography after Endovascular Treatment of Ruptured Intracranial Aneurysms - da Costa, Leodante; Dunkley, Benjamin T.; Bethune, Allison; Robertson, Amanda; MacDonald, Matt; Pang, Elizabeth (Frontiers in Neurology, 2016)
Objective: Amongst good outcome survivors of aneurysmal subarachnoid hemorrhage (aSAH), only 23% have normal neurocognitive performance, despite imaging that is often normal. The aim of this work is to explore the use of magnetoencephalography (MEG) after endovascular treatment of ruptured aneurysms. Methods: Good outcome aSAH patients treated with coiling and matched controls were recruited. Clinical assessments and resting-state MEG and anatomical MRI images were obtained. Brain space was normalized to standard Montreal Neurological Institute (MNI) brain. Areas of interest were identified with Automated Anatomical Labeling (AAL) and “virtual electrodes” reconstructed using vector beamformer. Spectral power density estimates for each location was averaged across the brain to derive mean signal power. Virtual-sensor data closest to the coil was assessed for signal quality. Results: Thirteen aSAH patients and 13 matched controls were recruited. Mean age was 54.5 years (SD=9.9) for controls and 56.8 years (SD=11.8) for aSAH. The majority of aneurysms (62%) were in the midline. Mean time from aSAH to MEG was 18.8 months (2.4 to 67.5; SD=19). Data quality was comparable in both groups, including the virtual-sensors close to the coil mass. Mean signal power showed no significant spectral alterations in the aSAH group. Conclusion: Magnetoencephalography is feasible in aSAH patients after endovascular treatment. Our results suggest that the signal quality and strength is good and the presence of coils does not interfere with testing. Considering the common neurocognitive complaints of aSAH survivors MEG could be developed to diagnose, quantify and monitor neurocognitive problems after aSAH.